Digital Media Use Activities Are Related to Students' Writing Skills and Competencies - Pratikno, Heru; Muttaqin, Zainul (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2024)
This study aims to determine how seriously students participate in learning Indonesian synchronously and asynchronously through digital lecture media, namely the Learning Management System (LMS). In addition, the researcher wanted to know how far the content quality of their writing was when they were given the task of writing a text and what factors influenced the cause of the quality level of their language skills. The methods used in this research are direct observation and questionnaires. The study results show that students are more enthusiastic when lectures are synchronous rather than asynchronous because they can listen directly to the explanations. In addition, the online media activities they engage in outside of class significantly impact the quality and quantity of their written content. Their activities usually include watching films, playing online games, and using social media.